Pengaruh Kualitas Pelayanan dan Harga PT GOJEK Terhadap Kepuasaan Konsumen GO-FOOD Di Padang - Zaky Wirananta; Syamsir Syamsir; Mutiara Rezika; Nurfaiza Nurfaiza; Irvan Rinaldi; Isratul Ilham Zet (Universitas Palangka Raya, 2022)
With the acceleration of the times and the progress of education, a prosperous economy, social and cultural changes and the development of advanced science and technology can facilitate human activities. This is in accordance with the concept of the Industrial Revolution 4.0, one of the characteristics of which is technological development and the digitalization era. Technological developments and digitalization can occur in several sectors, one of which is electronic trading or buying and selling on the Internet. Not only now, shopping can be done through social media such as the Instagram application, as well as online buying and selling applications that can be downloaded on smartphones. Given the high creativity of the younger generation, it is believed that it can increase Indonesia's per capita income, and adequate competitiveness will have a major impact on the development of online business. Of course, consumers will also be facilitated in their consumption activities. . The ease of doing business has aroused consumer interest in doing business, not only in the field of selling goods, now it can also be done online in the service sector, for example the Gojek application for online motorcycle taxis.